1995
DOI: 10.1177/016502549501800206
|View full text |Cite
|
Sign up to set email alerts
|

Using the HOME Inventory with Infants in Costa Rica

Abstract: This study determined the psychometric properties of the HOME (Home Observation for Measurement of the Environment) Inventory in a Latin American sample. HOME data for 183 healthy Costa Rican infants were compared to the original HOME standardisation sample from Little Rock. The Costa Rican total HOME average of 29.8 ± 6.7 was similar to the scores of families in Little Rock (mean = 31.2 ± 7.3). Measures or internal consistency and factor structure were similar in US and Costa Rican samples. In contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
2
23
0
2
Order By: Relevance
“…Neither did Grantham-McGregor et al (1992, unpublished) find differences in IT-HOME scores for 129 stunted and 32 non-stunted children. Similar to findings from US studies, Lozoff et al (1995) observed low correlations between the IT-HOME and MDI when children were 12-24 months old. However, after controlling for a variety of other variables, IT-HOME total made a significant contribution to the prediction of MDI scores for Costa Rican infants 12-23 months old (Lozoff et al, 1987).…”
supporting
confidence: 85%
“…Neither did Grantham-McGregor et al (1992, unpublished) find differences in IT-HOME scores for 129 stunted and 32 non-stunted children. Similar to findings from US studies, Lozoff et al (1995) observed low correlations between the IT-HOME and MDI when children were 12-24 months old. However, after controlling for a variety of other variables, IT-HOME total made a significant contribution to the prediction of MDI scores for Costa Rican infants 12-23 months old (Lozoff et al, 1987).…”
supporting
confidence: 85%
“…Responsiveness scores for children in Paraguay, Argentina, and St Vincent's were lower than US norms (Blevins-Knabe & Austin, 2000;Centro de Estudios Sobre Nutricion Infantil, 1996;Durbrow, Jones, Bozoky, Jimerson, & Adams, 1996); but scores in Costa Rica and Chile were not much lower (Bulnes, Cajdler, Edwards, & Lira, 1979;Castillo-Durin et al, 2001;Lozoff et al, 2003;Lozoff, Park, Radan, & Wolf, 1995;Tippie, 2003). Performance on certain indicators of responsiveness appear particularly revealing regarding cultural differences.…”
Section: Stimulation/teachingmentioning
confidence: 97%
“…One of the most common adjustments made to HOME in less affluent countries was to reduce the number of books and learning materials required to obtain credit for certain items (Aina et al, 1993;Drotar et al, 1999;Grantham-McGregor et al, 1995;Holding, 2003;Lozoff et al, 1995;Richter & Grieve, 1991;Zeitlin et al, 1995). Aina and colleagues (1993) changed cut-points for some HOME items (requiring 2 rather than 10 books) and included a focus on nonmanufactured objects (Note: the same decision about changing cut-points for books was made for the UNICEF child indicators project).…”
Section: Stimulation/teachingmentioning
confidence: 99%
“…El HOME es una escala construida para detectar indicadores de la cantidad y calidad del apoyo social, emocional y cognitivo disponible para el niño en su hogar. Ha sido ampliamente utilizado y ha resultado ser sensible a la detección de características familiares al ser aplicada en poblaciones latinoamericanas 10,11,22 . Esta medición fue realizada durante una visita sorpresa al hogar cuando el niño tenía 10 meses de edad.…”
Section: Evaluación Del Ambiente Del Niñounclassified